European drive to whistleblowing and integrity agencies - Sierra Rodríguez, Javier (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
The transposition of the Directive on whistleblower protection must be carried out in Spain before the end of 2021, which will force the incorporation into our internal law, with a general scope a range of alert channels, whistleblower guaranties and also independent authorities that must manage external reporting channels. This article examines the possible models to follow and the powers that this type of authority should have. From the examination of the different alternatives, reflection is invited so that not only the creation of a new authority is contemplated, but also the possible attribution of the whistleblowing system to existing control organisms, or even go towards a different model based on experience of the Italian anti-corruption agency that works in related fields such as transparency, public procurement and the fight against corruption.
Keywords: Whistleblowing; alerts; integrity; fight against corruption